The CUL7 E3 Ubiquitin Ligase Targets Insulin Receptor Substrate 1 for Ubiquitin-Dependent Degradation - Xu, Xinsong (2008)
Recent genetic studies have documented a pivotal growth-regulatory role played by the Cullin 7 (CUL7) E3 ubiquitin ligase complex containing the Fbw8-substrate-targeting subunit, Skp1, and the ROC1 RING finger protein. In this report, we identified insulin receptor substrate 1 (IRS-1), a critical mediator of the insulin/insulin-like growth factor 1 signaling, as a proteolytic target of the CUL7 E3 ligase in a manner that depends onmammalian target of rapamycin and the p70 S6 kinase activities. Interestingly, while embryonic fibroblasts of Cul7(−/−) mice were found to accumulate IRS-1 and exhibit increased activation of IRS-1’s downstream Akt and MEK/ERK pathways, these null cells grew poorly and displayed phenotypes reminiscent of those associated with oncogene-induced senescence. Taken together, our findings demonstrate a key role for the CUL7 E3 in targeting IRS-1 for degradation, a process that may contribute to the regulation of cellular senescence.